2020
DOI: 10.3390/cells9092128
|View full text |Cite
|
Sign up to set email alerts
|

EpCAM as Modulator of Tissue Plasticity

Abstract: The Epithelial Cell Adhesion Molecule or EpCAM is a well-known marker highly expressed in carcinomas and showing a strong correlation with poor cancer prognosis. While its name relates to its proposed function as a cell adhesion molecule, EpCAM has been shown to have various signalling functions. In particular, it has been identified as an important positive regulator of cell adhesion and migration, playing an essential role in embryonic morphogenesis as well as intestinal homeostasis. This activity is not due… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 63 publications
0
10
0
Order By: Relevance
“…EpCAM serves mainly as a homophilic cell adhesion molecule, but it has also been linked to roles in proliferation, differentiation, and cell-migration with differing levels of expression [ 113 ]. In the early stages of embryonic development, EpCAM is not expressed solely by epithelial cells, indicating a greater role of EpCAM plasticity and early development, and through the use of knock-out studies in Zebrafish, loss of EpCAM is linked to lethality and loss of tissue integrity, displaying the dual role of EpCAM in adhesion and motility [ 114 , 115 ]. EpCAM also plays a role in the assembly of adherens junctions as shown by the dramatic decrease in mRNA and protein expression of nectin1, a molecule involved in regulating the assembly of adherens and tight junctions, in EpCAM mutant mice [ 116 ].…”
Section: Overview On Oncogenic Emt: Emt-associated Biomarkersmentioning
confidence: 99%
“…EpCAM serves mainly as a homophilic cell adhesion molecule, but it has also been linked to roles in proliferation, differentiation, and cell-migration with differing levels of expression [ 113 ]. In the early stages of embryonic development, EpCAM is not expressed solely by epithelial cells, indicating a greater role of EpCAM plasticity and early development, and through the use of knock-out studies in Zebrafish, loss of EpCAM is linked to lethality and loss of tissue integrity, displaying the dual role of EpCAM in adhesion and motility [ 114 , 115 ]. EpCAM also plays a role in the assembly of adherens junctions as shown by the dramatic decrease in mRNA and protein expression of nectin1, a molecule involved in regulating the assembly of adherens and tight junctions, in EpCAM mutant mice [ 116 ].…”
Section: Overview On Oncogenic Emt: Emt-associated Biomarkersmentioning
confidence: 99%
“…EpCAM is related to several signaling pathways including the intramembrane protein hydrolysis (RIP)-mediated signaling and the activation of Wnt signaling to impact on tumor cell proliferation [ 41 ]. Today, EpCAM is reckoned as a marker highly expressed in carcinomas and extremely correlated with poor prognosis [ 42 ]. A large retrospective study using tissue microarrays showed that high level of EpCAM expression was found in 94.1% of patients with lung, colon, and prostate cancers and observed a significant reverse correlation between EpCAM expression and survival time [ 43 ].…”
Section: Targeting Antigensmentioning
confidence: 99%
“…Benign epithelia express EpCAM at a variable but generally lower level compared with carcinoma cells ( 41 ). EpCAM can modulate cell migration, proliferation and differentiation, and also prevent cell-cell adhesion ( 42 , 43 ). Vimentin is a well-known marker of EMT ( 44 , 45 ).…”
Section: Discussionmentioning
confidence: 99%